Constructing a Theory of Accounting–An Axiomatic Approach. - Carlson, Marvin L.; Lamb, James W. (The Accounting Review, 1981)
Abstract ABSTRACT: This paper gives certain fundamental portions of accounting theory–as it is currently understood and practiced–an axiomatic formulation in predicate logic. The nature of deductive systems is first described. Then the basic vocabulary of accounting is constructed from a base of primitive terms. A set of axioms is introduced and the rules of inference to be employed are enumerated. Theorems stating certain salient characteristics of financial position and income are then derived within the system. Finally, a prospectus is offered for further axiomatic research in accounting, including possible extensions of the system presented here.